1908. Social Risk Factors for COVID-19-Related Hospitalizations in Adults. (15th December 2022) - Reese, Olivia D; Tippett, Ashley; Hussaini, Laila; Salazar, Luis W; Taylor, Meg; Ciric, Caroline R; Castro, Khalel De; Taylor, Grace; Choi, Chris; Puzniak, Laura A; Hubler, Robin; Valluri, Srinivas; et al.
Abstract: Background: During the COVID-19 pandemic, social interventions such as social distancing and mask wearing have been encouraged. Social risk factors for SARS-CoV-2 infection and subsequent hospitalization remain uncertain. Methods: Adult patients were eligible if admitted to Emory University Hospital or Emory University Hospital Midtown with acute respiratory infection (ARI) symptoms (≤ 14 days) or an admitting ARI diagnosis from May 2021 – Feb 2022. After enrollment, an in-depth interview identified demographic and social factors (e.g., employment status, smoking history, alcohol use), household characteristics, and pandemic social behaviors. All patients were tested for SARS-CoV-2 using PCR. We evaluated whether these demographic and social factors were related to a positive SARS-CoV-2 test upon admission to hospital with ARI using a logistic regression model. Results: 1141 subjects were enrolled and had SARS-CoV-2 PCR results available (700 positive and 441 negative). The median age was greater in the SARS-CoV-2 negative cohort than in the positive cohort (60 and 53 years, respectively; P< .0001). Those who tested positive were more likely to have had at least some college education compared to those who tested negative (64.3% vs 52.3%, P< .0001; adjusted odds ratio [aOR]: 1.4 [95%CI: 1.1, 2.0]). Compared to those who tested negative, those who were SARS-CoV-2 positive were also more likely to be employed (48.9% vs 26.5%, P< .0001; aOR: 1.7 [95%CI: 1.1, 2.3]), have children 5-17 yo at home (27.6% vs 17.9%, P=.0002; aOR: 1.5 [95%CI: 1.1, 2.1]). Those with COVID-19 were less likely to receive home healthcare (6.2% vs 13.3%, P< .0001; aOR: 0.5 [95%CI: 0.4, 0.9]) and to be a current or previous smoker (7.6% vs 17.7%, P< .0001; aOR: 0.3 [95%CI: 0.2, 0.5]). Conclusion: Among adults admitted to the hospital for ARI, those who tested positive for SARS-CoV-2 were typically younger, more likely to care for school-aged children, more likely to work outside the home, but were less likely to receive home healthcare or smoke. Personal and public health strategies to mitigate COVID-19 should take into consideration modifiable social risk factors. Disclosures: Laura A. Puzniak, PhD. MPH, Merck & Co., Inc.: Stocks/Bonds|Pfizer, Inc.: Stocks/Bonds Robin Hubler, MS, Pfizer Inc.: Employee|Pfizer Inc.: Stocks/Bonds Srinivas Valluri, PhD, Pfizer: Employee|Pfizer: Stocks/Bonds Benjamin Lopman, PhD, Epidemiological Research and Methods, LLC: Advisor/Consultant Satoshi Kamidani, MD, NIH: His institution (Emory University) receives funds from Pfizer for his work as a co-investigator on clinical trials of Pfizer COVID-19 vaccine.|Pfizer: His institution (Emory University) receives funds from Pfizer for his work as a co-investigator on clinical trials of Pfizer COVID-19 vaccine. Christina A. Rostad, MD, BioFire Inc, GSK, MedImmune, Micron, Merck, Novavax, PaxVax, Pfizer, Regeneron, Sanofi-Pasteur.: Grant/Research Support|Meissa Vaccines, Inc.: Co-inventor of RSV vaccine technology licensed to Meissa Vaccines, Inc.|NIH (Funding from NIH to conduct clinical trials of Moderna and Janssen COVID-19 vaccines): Grant/Research Support John M. McLaughlin, PhD, Pfizer: Employee|Pfizer: Stocks/Bonds Evan J. Anderson, MD, GSK: Advisor/Consultant|GSK: Grant/Research Support|Janssen: Advisor/Consultant|Janssen: Grant/Research Support|Kentucky Bioprocessing, Inc: Data Safety Monitoring Board|MedImmune: Grant/Research Support|Medscape: Advisor/Consultant|Merck: Grant/Research Support|Micron: Grant/Research Support|NIH: Funding from NIH to conduct clinical trials of Moderna and Janssen COVID-19 vaccines|PaxVax: Grant/Research Support|Pfizer: Advisor/Consultant|Pfizer: Grant/Research Support|Regeneron: Grant/Research Support|Sanofi Pasteur: Advisor/Consultant|Sanofi Pasteur: Grant/Research Support|Sanofi Pasteur: Data Adjudication and Data Safety Monitoring Boards|WCG and ACI Clinical: Data Adjudication Board.